Marketing Strategy and Added Value of Halal Certification in Herbalife Beverage Business Development - Ira Mayasha; Rasta Kurniawati Br Pinem (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Health" is a difficult word to define, but health is very important in our lives. Islam can be interpreted as the results achieved by individuals or groups. Considering that Indonesia is the country with the largest Muslim population in the world, halal certification is a basic requirement for every product sold. The purpose of this study is to contribute to formulating an effective strategy for the development of Herbalife's business in the country. The research method used is a qualitative approach. The data collection method used in this study is interviews. The data analysis method in this study is data reduction, data presentation, and conclusion. The study results indicate that a marketing strategy that integrates halal certification can positively impact the Herbalife beverage business. By implementing the right market segmentation, product differentiation, and effective promotion and distribution strategies, Herbalife can increase its competitiveness in the global market. Halal certification is not only a requirement for regulatory compliance, but also an important factor in increasing consumer loyalty and expanding market reach. Therefore, the researcher suggests that a marketing strategy that integrates halal certification can positively impact the Herbalife beverage business. By implementing appropriate market segmentation, product differentiation, and effective promotion and distribution strategies, Herbalife can increase its competitiveness in the global market.